2021
DOI: 10.3389/fnins.2021.730879
|View full text |Cite
|
Sign up to set email alerts
|

FLAIR and ADC Image-Based Radiomics Features as Predictive Biomarkers of Unfavorable Outcome in Patients With Acute Ischemic Stroke

Abstract: At present, it is still challenging to predict the clinical outcome of acute ischemic stroke (AIS). In this retrospective study, we explored whether radiomics features extracted from fluid-attenuated inversion recovery (FLAIR) and apparent diffusion coefficient (ADC) images can predict clinical outcome of patients with AIS. Patients with AIS were divided into a training (n = 110) and an external validation (n = 80) sets. A total of 753 radiomics features were extracted from each FLAIR and ADC image of the 190 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Zhang et al ( 5 ) developed the machine learning model-based diffusion weighed imaging (DWI)/ADC radiomic features to classify ischemic stroke onset time. Quan et al ( 8 ) constructed the unfavorable outcome model based on the radiomic feature extracted from FLAIR and ADC image. Moreover, susceptibility weighted imaging (SWI), reflecting the oxygen extraction fraction of brain tissues, has been demonstrated as a useful predictor of early infarct size and early-stage clinical prognosis in acute ischemic stroke ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al ( 5 ) developed the machine learning model-based diffusion weighed imaging (DWI)/ADC radiomic features to classify ischemic stroke onset time. Quan et al ( 8 ) constructed the unfavorable outcome model based on the radiomic feature extracted from FLAIR and ADC image. Moreover, susceptibility weighted imaging (SWI), reflecting the oxygen extraction fraction of brain tissues, has been demonstrated as a useful predictor of early infarct size and early-stage clinical prognosis in acute ischemic stroke ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics is a novel developed data analysis technique that can transform medical images into high-throughput quantitative features, assess the heterogeneity of diseased tissue, and reflect the physiological and pathological status and has been applied to the prediction of clinical outcomes. At present, radiomics has a promising application prospect in stroke, including the diagnosis of stroke (Peter et al, 2017),early prediction of clinical outcome (Wen et al, 2020) and evaluation of medium and long term prognosis (Tang et al, 2020;Quan et al, 2021;Wang et al, 2021;Zhou et al, 2022). Wen et al (2020) developed a model based on radiological features extracted from computed tomography non-contrast computed tomography (NCCT) and computed tomography angiography (CTA) to predict the development of malignant acute middle cerebral Artery Infarction (mMCAi) in patients with cerebral infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Wen et al (2020) developed a model based on radiological features extracted from computed tomography non-contrast computed tomography (NCCT) and computed tomography angiography (CTA) to predict the development of malignant acute middle cerebral Artery Infarction (mMCAi) in patients with cerebral infarction. Several recent studies have shown that the clinical-radiomics model extracted from diffusion-weighted imaging (DWI), fluid attenuated inversion recovery (FLAIR) or apparent diffusion coefficient (ADC) achieved satisfactory performance in predicting AIS outcomes (Tang et al, 2020;Quan et al, 2021;Wang et al, 2021;Zhou et al, 2022). Most patients with ischaemic stroke receive only routine sequences, including DWI, ADC and FLAIR.…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics can facilitate better clinical decision by improving the process of detecting heterogeneous findings without visible abnormalities in medical images through high-throughput quantitative analysis of statistical features (Gillies et al, 2016 ). Successful applications of radiomics in acute stroke have been reported in prediction of the hematoma expansion (Ma et al, 2019 ; Xie et al, 2020 ; Liu et al, 2021 ; Song et al, 2021 ), successful recanalization (Qiu et al, 2019 ; Hofmeister et al, 2020 ), recurrence (Tang et al, 2022 ) and functional outcome (Haider et al, 2021 ; Quan et al, 2021 ; Wang et al, 2021 ). The discrimination of hematomas etiologies (Zhang et al, 2019 ; Nawabi et al, 2020 ) using radiomics analysis had been reported as well.…”
Section: Introductionmentioning
confidence: 99%